Beyond good deeds: how psychological capital drives under the lens of individual characteristics? - Sondang Talenta Noviana Simamora; Heru Kristanto (Indonesia Research and Study Center, 2026)
The phenomenon of burnout among Generation Z and millennial employees has emerged as a serious challenge, leading to decreased productivity and increased turnover rates. Toxic work environments and the lack of psychological capital development have exacerbated this issue, contributing to the voluntary resignation of over 70 percent of employees during the so-called “Great Resignation.” The education sector is particularly vulnerable due to limited resources and high workloads. This study aims to analyze the role of psychological capital and individual characteristics on organizational citizenship behavior (OCB), while also examining the moderating effect of individual characteristics on this relationship. Grounded in the Conservation of Resources (COR) theory, this research adopts a quantitative approach through a survey design. Data were collected from 203 employees working under educational foundations, selected using purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) with the assistance of AMOS 24 software. The findings reveal that both psychological capital and individual characteristics significantly and positively influence OCB (p < 0.05). Furthermore, individual characteristics moderate the relationship between psychological capital and OCB. These results highlight the importance of a holistic human resource development approach that integrates psychological capital and individual traits to foster resilient, committed, and prosocial behaviors among employees in resource-constrained educational organizations.